FEASIBILITY OF THE POCKET BOOK OF ADDITIVE SUBSTANCE SUBMATERIALS FOR JUNIOR HIGH SCHOOL AS A RESULT OF TESTING CARROT JUICE (Daucus carota L.) TO CHICKEN MEATBALLS’ SHELF LIFE AND ITS ORGANOLEPTIC - Sa'adah Purnamasari; Ruqiah Ganda Putri Panjaitan; Eko Sri Wahyuni (Universitas Negeri Padang, 2021)
This study aims to determine the feasibility of a pocket book as a learning medium for class VIII additives teaching materials based on the test results of the effect of carrot juice on shelf life and organoleptics of chicken meatballs. The background of making pocket book media is based on the results of interviews at SMP Negeri 10 Pontianak which said that the teaching and learning process was ineffective due to the lack of learning media. Therefore, the pocket book media is used as a learning medium. This study uses the Research and Development (R&D) method which consists of potentials and problems, data collection, product design, design validation, and design revision. The product design in this study is to make a pocket book by adding food additives and the results of the author's research. The pocket book media was validated by 5 validators, namely 3 teachers of SMP Negeri Pontianak and 2 Lecturers of Biology Education at the University of Tanjungpura. This pocket book media is measured from the aspects of the feasibility of format, content, and language which consists of 11 criteria. Based on the results of the pocket book validation, it was obtained CVI value of 1 for all criteria with an average validity value of 4 so that the pocket book media was declared valid and could be used as a learning media for additive sub material.